A dodging algorithm to reconfigure photovoltaic array to negate partial shading effect - Ramasamy, Sridhar; Seenithangam, Jeevananthan; Dash, Subhransu Sekhar; Chaitanya, Krishna (Progress in photovoltaics, 2016)
The efficiency of photovoltaic (PV) power system is hampered to a large extent when it is shaded even by a fraction. The performance dwindle in PV array due to partial shading is not proportional to the volume of shading, rather it depends on pattern of shading, array configuration, and site where PV panels are installed. Total cross‐tied (TCT) is the proven scheme among all the prevailing interconnection schemes like series, parallel, series–parallel (SP), and bridge linked to negate partial shading impact. This work aims at proposing a new adaptive algorithm to reconfigure the PV array such that it evades the shading effect. Also, it suggests a unique PV panel arrangement for a familiar shading pattern by which the shading prospects are reduced considerably. The proposed work has a clear edge over the TCT method in managing shading, ruling out multiple peaks in output power curve. This technique is highly recommended for constant power loads as the output current is maintained constant, setting aside the varying atmospheric conditions, whereas other reconfiguring techniques do not address this application. The suggested topology is simulated in matlab/Simscape environment for a 3 × 3 PV array and realized in a hardware prototype where a digital signal controller Dspic30f4011 is used to impart the proposed control algorithm. Copyright © 2015 John Wiley & Sons, Ltd. The efficiency of photovoltaic (PV) power system is hampered to a large extent when it is shaded even by a fraction. The performance dwindle in PV array due to partial shading is not proportional to the volume of shading, rather it depends on pattern of shading, array configuration, and site where PV panels are installed. This work aims at proposing a new adaptive algorithm to reconfigure the PV array such that it evades the shading effect.